Evolving interactions between diazotrophic cyanobacterium and phage mediate nitrogen release and host competitive ability. Issue 12 (December 2016) - Cairns, Johannes; Coloma, Sebastián; Sivonen, Kaarina; Hiltunen, Teppo
Abstract : Interactions between nitrogen-fixing (i.e. diazotrophic) cyanobacteria and their viruses, cyanophages, can have large-scale ecosystem effects. These effects are mediated by temporal alterations in nutrient availability in aquatic systems owing to the release of nitrogen and carbon sources from cells lysed by phages, as well as by ecologically important changes in the diversity and fitness of cyanobacterial populations that evolve in the presence of phages. However, ecological and evolutionary feedbacks between phages and nitrogen-fixing cyanobacteria are still relative poorly understood. Here, we used an experimental evolution approach to test the effect of interactions between a common filamentous, nitrogen-fixing cyanobacterium ( Nodularia sp.) and its phage on cellular nitrogen release and host properties. Ecological, community-level effects of phage-mediated nitrogen release were tested with a phytoplankton bioassay. We found that cyanobacterial nitrogen release increased significantly as a result of viral lysis, which was associated with enhanced growth of phytoplankton species in cell-free filtrates compared with phage-resistant host controls in which lysis and subsequent nutrient release did not occur after phage exposure. We also observed an ecologically important change among phage-evolved cyanobacteria with phage-resistant phenotypes, a short-filamentous morphotype with reduced buoyancy compared with the ancestral long-filamentous morphotype. Reduced buoyancy might decrease the ability of these morphotypes to compete for light compared with longer, more buoyant filaments. Together, these findings demonstrate the potential of cyanobacteria–phage interactions to affect ecosystem biogeochemical cycles and planktonic community dynamics.